"Be Real Black for Me": Imagining BlackCrit in Education. (April 2016) - Dumas, Michael J.; ross, kihana miraya
The authors put forward a theorization of a Black Critical Theory, or what might be called BlackCrit, within, and in response to, Critical Race Theory, and then outline ways that BlackCrit in education helps us to more incisively analyze how the specificity of (anti)blackness matters in explaining how Black bodies become marginalized, disregarded, and disdained in schools and other spaces of education.